A Shorter Version of the Happiness-Increasing Strategies Scale in the Indian Context - Kamlesh Singh; Naina Nagpal; Shefali Midha; Deepika Chahal (SAGE Open)
This study aims to examine the psychometric properties of the English and Hindi versions of the Happiness Increasing Strategies Scale in the Indian context. Data were collected online from 581 participants. Confirmatory factor analysis was conducted to test the original 8-factor model, following which exploratory factor analysis was conducted to determine a more suitable factor solution. The study also examined gender differences in the choice of strategies. The results did not confirm the original 8-factor model. However, an 8-factor solution for both the original and Hindi-translated version constituting 36 items demonstrated acceptable psychometric properties, good internal consistency, and significant correlations with the validating scales measuring mental and general well-being, harmony in life, and peace of mind. The 36-item Happiness Increasing Strategies Scale constituting 8 factors demonstrated a more appropriate factor solution in the Indian context. Females reported a significantly higher mean on Social Interaction, Instrumental Goal Pursuit, and Religion & Mental Control.